Bisphenol A: an emerging threat to female fertility - Claudia Pivonello; Giovanna Muscogiuri; Antonio Nardone; Francesco Garifalos; Donatella Paola Provvisiero; Nunzia Verde; Cristina de Angelis; Alessandro Conforti; Mariangela Piscopo; Renata Simona Auriemma; Annamaria Colao; Rosario Pivonello (BMC, 2020)
Abstract Bisphenol-A (BPA) has been reported to be associated to female infertility. Indeed, BPA has been found to be more frequently detected in infertile women thus leading to hypothesize a possible effect of BPA on natural conception and spontaneous fecundity. In addition, in procedures of medically assisted reproduction BPA exposure has been found to be negatively associated with peak serum estradiol levels during gonadotropin stimulation, number of retrieved oocytes, number of normally fertilized oocytes and implantation. BPA deleterious effects are more critical during perinatal exposure, causing dysregulation of hypothalamic-pituitary-ovarian axis in pups and adults, with a precocious maturation of the axis through a damage of GnRH pulsatility, gonadotropin signaling and sex steroid hormone production. Further, BPA exposure during early lifestage may have a transgenerational effect predisposing the subsequent generations to the risk of developing BPA related disease. Experimental studies suggested that prenatal, perinatal and postnatal exposure to BPA can impair several steps of ovarian development, induce ovarian morphology rearrangement and impair ovarian function, particularly folliculogenesis, as well as can impair uterus morphology and function, in female adult animal and offspring. Finally, studies carried out in animal models have been reported the occurrence of endometriosis-like lesions after BPA exposure. Moreover, BPA exposure has been described to encourage the genesis of PCOS-like abnormalities through the impairment of the secretion of sex hormones affecting ovarian morphology and functions, particularly folliculogenesis. The current manuscript summarizes the evidence regarding the association between BPA exposure and female infertility, reviewing both clinical and preclinical studies.